Bioengineered heart valves for personalized therapy: advances in manufacturing and clinical challenges - Saeed, Mahnoor; Khan, Kamran A. (Frontiers in Bioengineering and Biotechnology, 2026)
Valvular heart diseases (VHDs) remain a significant clinical challenge, with mechanical and bioprosthetic valves offering only temporary solutions and failing to address long-term complications such as structural degradation, immune rejection, and the inability to dynamically remodel. Over the past two decades, tissue-engineered heart valves (TEHVs) have emerged as a promising alternative, combining biomaterials and patient-specific strategies to overcome these limitations. However, persistent issues, such as immune rejection, poor hemocompatibility, and inconsistent remodeling - continue to hinder clinical translation. Recent advances in immunomodulation, scaffold engineering, and personalized therapies show promise in mitigating these challenges, yet a fully integrated, comprehensive strategy remains elusive. This review critically explores the convergence of TEHVs and immunomodulation, focusing on how biomaterial-based immune engineering, nanoparticle-driven tolerance strategies, and advanced scaffold design can reshape heart valve therapy. By synthesizing recent innovations and highlighting key translational gaps, this paper lays the groundwork for a new generation of TEHVs that integrate, adapt, and regenerate, moving beyond passive mechanical replacements toward truly personalized cardiovascular solutions.